Contribution Of Islamic Boarding School In Character Formation Of Students At Bahrul Ulum Islamic Boarding School Pujon Malang - Atabik, Royyan; Arifin, Badrul (Al-Fikru: Jurnal Ilmiah, 2025)
This study investigates the contribution of Bahrul Ulum Islamic Boarding School in Pujon, Malang, to the character development of its students. Employing a qualitative descriptive approach, the research focuses on the strategies implemented by the pesantren, as well as the supporting and inhibiting factors in the character-building process. Data were collected through observation, in-depth interviews, and literature review, and were analyzed using an interactive method until reaching saturation. The findings reveal that the pesantren plays a pivotal role in shaping students’ social character through four main strategies: instructional activities, role modeling, habituation, and the use of advice and corrective punishment in an educational manner. Supporting factors include students’ intrinsic motivation, the conducive environment of the pesantren, and the availability of adequate facilities and infrastructure. Conversely, challenges arise from limited teacher quality and financial constraints. These results highlight that pesantren function not only as religious educational institutions but also as strategic agents of social and moral development, significantly contributing to the formation of disciplined, responsible, and morally upright students.